Magnetic Nanoparticles and Magnetic Field Exposure Enhances Chondrogenesis of Human Adipose Derived Mesenchymal Stem Cells But Not of Wharton Jelly Mesenchymal Stem Cells - Labusca, Luminita; Herea, Dumitru-Daniel; Emanuela Minuti, Anca; Stavila, Cristina; Danceanu, Camelia; Plamadeala, Petru; Chiriac, Horia; Lupu, Nicoleta (Frontiers in Bioengineering and Biotechnology, 2021)
PURPOSE: Iron oxide based magnetic nanoparticles (MNPs) are versatile tools in biology and medicine. Adipose derived mesenchymal stem cells (ADSCs) and Wharton Jelly mesenchymal stem cells (WJMSCs) are currently tested in different strategies for regenerative (RM) purposes. Their superiority compared to other mesenchymal stem cell consists in larger availability, superior proliferative and differentiation potential. Magnetic field (MF) exposure of MNP loaded MSCs has been proposed as a method to deliver mechanical stimulation for increasing conversion to musculoskeletal lineages. In this study we investigated comparatively chondrogenic conversion of ADSC-MNPs and WJMSCs with or without MF exposure in order to detect the most appropriate cell source and differentiation protocol for future cartilage engineering strategies. METHODS. Human primary ADSCs and WJMSCs from various donors were loaded with proprietary as prepared MNPs. The effect on proliferation and cellular senescence (beta galactosidase assay) in long term culture in vitro was assessed. Chondrogenic differentiation in vitro in pellet culture system with or without MF exposure was assessed using pellet histology (Safranin O staining) as well as quantitative evaluation of glycosaminoglycan (GAG) deposition per cell. RESULTS. ADSC-MNP complexes displayed superior proliferative capability and decreased senescence after long term (28 days) culture in vitro compared to non-loaded ADSC and to WJMSC-MNP. Significant increase in chondrogenesis conversion in terms of GAG/cell ratio could be observed in ADSC-MNP. MF exposure increased GAG deposition in MNP loaded ADSCs but not in WJMSCs. CONCLUSION. ADSC-MNP display decreased cellular senescence and superior chondrogenic capability in vitro compared to non-loaded cells as well as to WJMSC-MNPs. MF exposure further increases ADSC-MNP chondrogenesis in ADSCs but not in WJMSCs. Loading ADSCs with MNPs can derive a successful procedure for obtaining improved chondrogenesis in ADSCs. Further in vivo studies are needed to confirm the utility of ADSC-MNP complexes for cartilage engineering.